(Com) viver e (com) fiar uma rede quente na experiência sensível de vinculação afetiva : uma análise das práticas de acolhimento infanto-juvenil no município de Vitória/ES - Tristão, Valeska Campos (2015)
From our experience in the Special Social Protection of High Complexity for children and adolescents from Vitória (wich includes foster and institutional care), we seek to follow the controversy that concerns these services, aiming to analyse the crossings that pervades the reality of these services like criminalization of poverty, family valorization, strengthening of foster care, disqualification of institutional spaces, the development of foster children, among others. We believed that even with these issues that cross over the care services, we can potentialize this network and invent new ways of relating it to life, to children, families and the protective measures services. Therefore, we are relying on the understanding of this network as transformation, alliances, flows, mediations and movements, as proposed by the Actor-Network Theory. The analytical devices used in this work were the field diary, the analysis of the minutes of the monthly meetings of the high complexity equipment for children and adolescents with the Childhood and Youth court of Vitória and interviews with actors who form the special social protection network of high complexity. The theme bond and trust emerges as a crossing agent of our interventions. Therefore, in order to produce a inflection in our research, we ally ourselves to ethical reflections that link us to the intensification of the trial, to the affective relationships and health practices, since betting on the power of family and institutional care modalities is betting on the relationship, in building bonds and trust.